DEVELOPMENT IN SPORT SCIENCES: DIFFERENCES IN THE TRAJECTORY OF WOMEN AND MEN DURING THE FORMATION COURSE OF COACHES - Yuka Sato dos Santos, Yura (2023)
In this study, the sports experiences and the relevant people in the trajectory of the students were qualitatively analyzed until the discipline “Sports Coaches and Coaches” of the Sport Sciences course at the State University of Campinas. We used Rappaport Timeline with 21 male and 8 female students. The women reported the influence of family members and Physical Education teachers. Men had positive experiences at school. Representativeness and access to sport were favorable to men and unfavorable to women. The lower presence of women on the course and as possible future coaches is associated with a trajectory of less access and opportunities to experience the sport.